Peningkatan Peran “REKAWANGI” Sebagai Pelaku Rantai Pasok Melalui Nilai Tambah Cokelat Praline di Desa Jambewangi, Kabupaten Banyuwangi - Yuli Hariyati; Indah Ibanah; Rena Yunita Rahman; Dyah Ayu Savitri; M. Ghufron Rosyady; Setiyono; Gatot Subroto (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
This community service activity aims to improve the knowledge and skills of the Young Farmers “REKAWANGI” of Jambewangi Village, Banyuwangi, in processing cocoa into value-added praline chocolate products. The activity was carried out for six participants through theoretical delivery and direct practice methods. The material provided included an introduction to processed cocoa products, praline chocolate making techniques, a simple tempering process, and chocolate product storage techniques. The practical stage was carried out through direct guidance starting from melting chocolate, molding pralines, filling, and product packaging. The results of the activity showed that participants were able to understand and practice the praline chocolate making process well. In addition, participants showed high enthusiasm and enthusiasm during the training. This activity is expected to support the improvement of young farmers' skills and open up business opportunities based on local cocoa processing that have the potential to improve the economy of the Jambewangi Village community, Banyuwangi.